WATER AND TOURISM IN THE FORMOSO RIVER BASIN IN BONITO-MS: TOURIST PERCEPTION - Silva, Priscila Varges da; Piroli, Edson Luis [UNESP]; Pinto, Andre Luiz (Univ Estadual Paulista Julio Mesquita Filho, 2016)
In many tourist destinations, the water resources are considered the most relevant element of tourist attraction. Water tourism gives value to water quality, since the water must have characteristics that can attract and satisfy tourists. Formoso River Basin is the most important watershed of Bonito-MS and most of the city's tourist attractions are related to water. This paper aimed to analyze the tourists' perception after their contact with water in order to understand its importance to the tourism in Formoso basin. The study was developed through literature review, interviews with tourists and data analysis. The results showed up that water truly exerts power of attraction and its transparency is one of the most important attractions of Bonito.
Keywords: Perception; Tourism; Tourist; Tourist Attractions; Water